INTEGRAL CURRICULUM MANAGEMENT BASED ON TAUHID - Yudi Ardian Rahman; Muhammad Rafiq Kurniawan; As’ad Daroini; A. Ansorullah (International Conference on Humanity Education and Society (ICHES), 2023)
Curriculum management is an integral part in educational curriculum development, which also requires concepts and procedures. Integral Elementary School of Luqman Al-Hakim Bondowoso is an educational institution that uses an integral curriculum based on monotheism in its learning process. Based on the results of research conducted at Integral Elementary School of Luqman Al-Hakim Bondowoso, it shows that the tauhid-based integral curriculum used is a combination curriculum from the Service curriculum with the Hidayatullah integral education curriculum and also the school culture developed at Integral Elementary School of Luqman Al-Hakim Bondowoso. Tauhid-based integral curriculum management includes preparation or steps when compiling the curriculum, implementing the curriculum and evaluating the curriculum and the purpose of using an integral monotheism-based curriculum is to produce output that is already listed on the school profile. The preparation process includes all elements of the school, starting from the school principal, vice principal for curriculum, teachers and school committees. In the process of implementation, all subject matter is linked to the propositions in the Al-Qur'an and Hadith. Meanwhile, curriculum evaluation is carried out every three months or every mid-semester regarding the learning carried out by the teacher and evaluation every week to see how far the school program has been successfully carried out.